Temperature sensitive synthesis of transfer RNAs in vivo in Saccharomyces cerevisiae. - Marschalek, R (1990)
Dictyostelium discoideum tRNA genes can be expressed efficiently in vivo in yeast, and transcription products are processed to mature tRNAs. However, primary transcripts of a variant tRNA(Val)(UAC) gene are processing deficient under standard growth conditions (30 degrees C), due to a slightly altered 5' flanking region. A stable extended amino acid acceptor stem, which seems to be required to compensate a G5-G68 mismatch, cannot form. This mismatch destabilizes secondary and probably tertiary structures to such an extent that recognition of processing enzyme(s) under normal conditions (30 degrees C) is impaired. Growing yeast cells at reduced temperature (22 degrees C) can phenotypically complement the processing defect. This observation provides a new concept for the temperature dependent expression of protein coding genes which carry a nonsense codon. Translation of corresponding messages can be controlled by products of a temperature sensitive su-tRNA gene. We successfully tested this concept with two amber suppressors derived from a tRNA(Glu)(UUC) gene from D. discoideum. One of the variant tRNA genes codes for a product with a destabilized amino acid acceptor stem. Primary transcripts of this particular su-tRNA(Glu)(CUA) gene are processed only at reduced growth temperatures and consequently function as temperature sensitive suppressors only under these conditions.